Error analysis : Investigating the paragraph writing of malaysian esl learners - Zuraina, Ali; Shahid, Shahid Hussain; Amy Zulaikha, Mohd Ali; Ahmed, Abubaker Hassan Bakri; Jayapalan, Evelyn (Universiti Malaysia Sarawak, 2023)
The study investigates an impromptu writing task administered to diploma students studying in one of the technical universities on the East Coast of Malaysia. In particular, it identifies grammatical errors in one-paragraph writing in terms of overall errors, most errors and least errors. The samples were 49 students undergoing the Preliminary Semester taking English as one of the subjects in the particular semester. The study found that students made errors to a certain degree in using articles, tenses, and subject-verb agreement (SVA), among others. More specifically, the highest number of errors students made were in tenses, SVA, and word choices, while the least errors were in possessive and attributive structures, gerunds, and infinitives. The results indicate that assigning students impromptu writing contributed to their performance errors. Despite their low vocabulary knowledge, it also made them less expressive when writing under such conditions.